Biathlon shooting as a model from a biomechanical, kinesiological and sport psychological perspective - a multidisciplinary approach - Finkenzeller, T.; Sattlecker, G.; Würth, S.; Buchecker, M.; Hoedlmoser, K.; Lindinger, S. J.; Amesberger, G. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INITIAL SITUATION: Since more than 15 years, shooting performance of Austrian and international biathletes is tested at the department of sport science and kinesiology of the University of Salzburg. The focus of diagnostics was attached to biomechanical parameters in order to provide knowledge about the athletes' shooting technique. This resulted in a refined practical knowledge about shooting in biathlon over the years. Consequently, it was pursued the goal to evaluate biomechanical data of shooting diagnostics scientifically. In the following years, conference papers, master theses and articles were published (e. g. Sattlecker, Buchecker, Birklbauer, Müller, & Lindinger, 2013; Sattlecker, Buchecker, Müller, & Lindinger, 2014). The intensive preoccupation with the aiming process of biathletes created the need to perform research from a multidisciplinary perspective.